Uma Proposta de Plataforma para Avaliação Contínua de Maturidade em Governança de Cibersegurança no Setor Público - Braga, João G. I.; Sousa, Francisco J. S.; Pereira, Paola S.; Nogueira, Tales P.; Silva, Antonia M. A. da; Rodrigues, Emanuel Bezerra; Cialdini, Alexandre S.; Andrade, Rossana M. C. (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2026: Anais Estendidos do XXVI Simpósio Brasileiro de Cibersegurança, 2026)
This paper proposes a web-based platform to support continuous cybersecurity maturity assessment in the public sector, aligned with the Information Privacy and Security Program (PPSI). Motivated by limitations of unstructured assessment practices, such as spreadsheet-based monitoring, the proposed solution centralizes sensitive information, supports evidence management, and improves traceability through role-based access and audit mechanisms. The platform operationalizes PPSI guidelines through structured forms, data analysis, dashboards, and action plans, enabling organizations to assess maturity levels, identify gaps, prioritize corrective measures, and monitor progress over successive evaluation cycles. By integrating governance, monitoring, and improvement activities, the solution will contribute to greater transparency, accountability, and consistency in cybersecurity management for public entities.